Emerging investigator series: dispersed transition metals on a nitrogen-doped carbon nanoframework for environmental hydrogen peroxide detection. Issue 8 (25th July 2018) - Li, Zehui; Jiang, Yuheng; Liu, Chenming; Wang, Zhuoya; Cao, Zhiqin; Yuan, Yi; Li, Mingjie; Wang, Yaling; Fang, Daliang; Guo, Zhuang; Wang, Dongbin; Zhang, Guangjin; et al.
Abstract : A Cu/Mn immobilized carbon nanoframework modified sensor was used for continuously detecting the H2 O2 concentration in an electro-Fenton system. Abstract : Hydrogen peroxide (H2 O2 ) is a key species in many environmental processes such as the electro-Fenton system to remove organic pollutants in wastewater treatment. Traditional methods for measuring H2 O2 are often complex and time-consuming. Due to their low cost and high catalytic activity, transition metals (TM) can be used as high-performance electrochemical sensing materials for detecting H2 O2 . However, the aggregation of metal atoms will severely limit their catalytic efficiency and exposure area. In this study, we explored a method to disperse TM homogeneously on a zeolitic imidazolate framework-8 (ZIF-8) derived nitrogen-doped carbon (N/C) nanoframework and used it as the electrocatalyst for detecting H2 O2 in an electro-Fenton system. Cu and Mn were used as the examples. Benefitting from the homogeneously dispersed TM, the synthesized nanoframework with a low content of TM exhibits superior electrocatalytic activity and an anti-interference ability in detecting H2 O2 . It has a wide linear range (0.0005–50 mM for 1% Cu–N/C and 0.0001–50 mM for 1% Mn–N/C) and a low detection limit (0.047 μM for 1% Cu–N/C and 0.036 μM for 1% Mn–N/C). Using the synthesized nanoframework, a system for continuously detecting the H2 O2 concentration in an electro-Fenton system in situ was presented. The reported method to fabricate such nanomaterials with a higher catalytic efficiency of TM has implications in other applications such as environmental treatment, catalysis, and energy conversion.